(untitled) (Ozone Therapy Global Journal, 2017)
The complex therapy of the patients with malignant and nonmalignant tumors of uterine includes radical surgery with hormonotherapy, polychemotherapy and radiation therapy. These methods have a whole number of side effects on a patient organism such as toxic and immuno- suppressive effects as well as balance of pro- and antioxidant systems disorders. In this connection it is important to include in complex postoperative therapy auxiliary methods of treatment, which reduce intoxication, modify antioxidant protection level, normalize lipid peroxidation intensity and immunity. One of such methods is ozone-therapy. Treatment of a whole number of diseases including cancers demonstrates positive effects. Immune system realizes elimination of tumor cells and restore the homeostasis of the organism. Reasonability of immunocorrecting therapy is identified if it changes immune cell repertoire and serum level of soluble immune cell membrane antigens or not. Also it is interesting to investigate lipid peroxidation process and antioxidant protection state. Some physicochemical forces can increase reactive oxygen species production and destroy tumor cells. So these forces can be used in anticancer therapy. In this connection the aim of our research was to study the immunologic status before and after treatment with ozonized physiological saline in gynecologic patients with malignant and nonmalignant tumors for pathogenetic justification of ozone usage in persons suffering from hysteromyoma and endometrial cancer in the post-surgical period..